We are probably not Sims - Mitchell, John B. O. (Science & Christian belief, 2020)
In this article, I discuss the current state of the debate around the simulation hypothesis, the idea that the world we inhabit is a computer simulation in or within another universe. Considering recent work from a range of authors, I suggest that statistical arguments in favour of a simulated world are naive and fail to account either for Ockham's Razor or for alternative existential possibilities besides base reality and a simulation. Most significantly, I observe that it would be computationally impossible in our own universe to simulate a similar cosmos at fine granularity. This implies substantial differences in size and information content between simulating and simulated universes. I argue that this makes serious analysis of the simulation argument extremely difficult. I suggest that Christian theology has no reason to reinvent itself to accommodate simulism; the two should be viewed as mutually exclusive world-views. Further, I note that the existence of a human soul or spirit, or indeed any non-reductionist explanation of human consciousness, could undermine the assumption of substrate independence that simulism requires.